Robots móviles Chapter 1 Introduction to expert systems - Savage Carmona, Jesús (My University, 1998)
Expert systems can be considered declarative programming because the programmer does not specify haw a program is to achieve its goal at the level of an algorithm. For example, in a rule-based expert system, any of the rules may become activated and put on the agenda it its LHS matches the facts.
Keywords: systems; program; symbolic; characteristic; execution